2020
DOI: 10.1002/adfm.202000693
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable MXene@Pt/SWCNTs' Nanocatalysts for Hydrogen Evolution Reaction

Abstract: Developing nano-or atom-scale Pt-based electrocatalysts for hydrogen evolution reaction (HER) is of considerable importance to mitigate the issues associated with low abundance of Pt. Here, a protocol for constructing a hierarchical Pt-MXene-single-walled carbon nanotubes' (SWCNTs) heterostructure for HER catalysts is presented. In the heterostructure, highly active nano/atom-scale metallic Pt is immobilized on Ti 3 C 2 T x MXene flakes (MXene@Pt) that are connected with conductive SWCNTs' network. The hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(117 citation statements)
references
References 43 publications
3
114
0
Order By: Relevance
“…The MXenes. [ 100 ] black phosphorous, [ 101 ] and MoS 2 [ 102 ] can be promising alternatives for single metals atoms anchoring, because of their stable and tunable nanostructure. There are already examples of successful applications using these materials for SACs.…”
Section: Discussionmentioning
confidence: 99%
“…The MXenes. [ 100 ] black phosphorous, [ 101 ] and MoS 2 [ 102 ] can be promising alternatives for single metals atoms anchoring, because of their stable and tunable nanostructure. There are already examples of successful applications using these materials for SACs.…”
Section: Discussionmentioning
confidence: 99%
“…The poor charge-transfer behaviour due to the restacking of MXenes may limit its application. Therefore, it is vital to develop a good strategy to prevent MXene restacking, such as introducing space vectors between the layers using CNTs 211 or by using the concentrated acid etching method. 212 Although achievements in the research and development of these materials have greatly progressed, there are still some challenges in their ORR activity and stability.…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…It has been found that Pt nanoparticles deposited on Ti 3 C 2 T x MXenes exhibit better HER activity with minimum Pt content [69][70][71][72]. In comparison, Wu et al synthesized Pt single atom, Pt nanoparticles, and Pt 3 Ti loaded Ti 3 C 2 T x using in situ co-reduction at different temperatures [73].…”
Section: Mxenes-supported Nanohybrids As Her Catalystsmentioning
confidence: 99%